Identification of a Pharmacological Biomarker for the Bioassay-Based Quality Control of a Thirteen-Component TCM Formula (Lianhua Qingwen) Used in Treating Influenza A Virus (H1N1) Infection - Gao, Dan; Niu, Ming; Wei, Shi-zhang; Zhang, Cong-en; Zhou, Yong-feng; Yang, Zheng-wei; Li, Lin; Wang, Jia-bo; Zhang, Hai-zhu; Zhang, Lan; Xiao, Xiao-he (Frontiers in Pharmacology, 2020)
As individual index component for quality control (QC) is difficult to guarantee the clinical effectiveness of traditional Chinese medicine (TCM), it is more significant to discover new method for QC to solve this imperious demand. Here, we chose a thirteen-component TCM formula - Lianhua Qingwen capsule (LHQW) as representative, to explore the pivotal biomarker for bioassay methodology to engage close association between QC methods and its efficacy. Initially we demonstrated that the chemical fingerprint can't effectively distinguish batches of LHQW. Then pharmacological experiments indicated that LHQW was effective to treat influenza A virus (H1N1) infection in the H1N1 infection mice model, as claimed in clinical trials, through improving pathologic alterations, body weight loss, virus replication and lung lesions and inflammation. Furthermore, by serum metabolomics analysis, we screened out two important metabolites, prostaglandin F2α and arachidonic acid, and their metabolic pathway - arachidonic acid metabolism as the vital indicators of LHQW efficacy for influenza. The subsequent macrophages transcriptomics highlighted the prominent role of cyclooxygenase-2 (COX-2), which is the major rate-limiting enzyme in the arachidonic acid metabolism pathway. Finally, COX-2 was validated in either the gene expression or the enzymatic activity especially in 43 different batches of LHQW including commercial samples and homemade destruction to be a viable biomarker for the establishment of bioassay for QC. Our study provides systematic methodology in the biomarker exploration for establishing the bioassay of LHQW or other TCM formula relating to the clinical efficacy and the mechanism.